PEREMPUAN DAN PENDIDIKAN ANAK - hasim, sarifa suhra (PSW, 2010)
The ideal women is the women who can be exist in a carrier but still keeping end up about islam personality. Such as a wife obeys husbandâs command, become a good mother to her children, educating them become a powerful islam generation, to be qualified man and be professional. The Muslim should be consistent about the teaching religion and should be filtered the bad of western people culture. By reason of this career is willing to sacrifice his personal interests and refused to take care the children when the western culture and its civilization were almost on the verge of destruction.Why the western culture and civilization criticize itself? Because the western civilization has not found the truth one in spiritual away, they felt unhappy , worried and not ease in his life. Apparently, this is not creating a harmony of relationship between parent and children, hence, in islam womenâs role in educating children is very vital and important.